Reformasi Hukum Waris: Memadukan Aspek Adat dan Agama demi Mewujudkan Keadilan dalam Pembagian Warisan - Riyanda, Arief Rahman (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
ABSTRACTThis article discusses the need for inheritance law reform that integrates customary and religious aspects to achieve justice in the distribution of inheritance. In a heterogeneous society with cultural diversity and religious beliefs, it is important to accommodate strong customary values and high-principled religious principles in the inheritance legal process. Inheritance law reform that combines customary and religious aspects can create equality in inheritance distribution while respecting traditions and beliefs embedded in the community. The article explains that through the introduction of inclusive legal regulations and dispute resolution mechanisms based on customary and religious principles, justice can be achieved. In this context, the article also emphasizes the importance of cooperation among legal institutions, legal experts, customary leaders, and religious figures in formulating fair legal policies. Thus, the article highlights that inheritance law reform that integrates customary and religious aspects is not only important for achieving justice in inheritance distribution but also strengthens cultural diversity and tolerance in society.